2020
DOI: 10.1002/ece3.6304
|View full text |Cite
|
Sign up to set email alerts
|

Historical translocations and stocking alter the genetic structure of a Mediterranean lobster fishery

Abstract: Stocking is often used to supplement wild populations that are overexploited or have collapsed, yet it is unclear how this affects the genetic diversity of marine invertebrate populations. During the 1970s, a lobster stock enhancement program was carried out around the island of Corsica in the Mediterranean using individuals translocated from the Atlantic coast of France. This included the release of thousands of hatchery‐reared postlarval lobsters and several adult individuals, but no monitoring plan was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Previous studies have explored European lobster population structure at different geographical scales using novel and traditional markers, i.e., RAPDS ( Ulrich et al, 2001 ), allozymes ( Jørstad et al, 2005 ), mtDNA and RFLPs ( Triantafyllidis et al, 2005 ), microsatellites ( Huserbråten et al, 2013 ; Watson et al, 2016 ; Ellis et al, 2017 ) and SNPs ( Jenkins et al, 2019 , 2020 ). At the broad geographical scale, coherent patterns of gene flow discontinuity were observed where several major distinct groups, i.e., Atlantic, northern Norway, Netherlands and Mediterranean were identified with the presence of an IBD pattern at the European level (for more detail see Triantafyllidis et al, 2005 ; Ellis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored European lobster population structure at different geographical scales using novel and traditional markers, i.e., RAPDS ( Ulrich et al, 2001 ), allozymes ( Jørstad et al, 2005 ), mtDNA and RFLPs ( Triantafyllidis et al, 2005 ), microsatellites ( Huserbråten et al, 2013 ; Watson et al, 2016 ; Ellis et al, 2017 ) and SNPs ( Jenkins et al, 2019 , 2020 ). At the broad geographical scale, coherent patterns of gene flow discontinuity were observed where several major distinct groups, i.e., Atlantic, northern Norway, Netherlands and Mediterranean were identified with the presence of an IBD pattern at the European level (for more detail see Triantafyllidis et al, 2005 ; Ellis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited gene flow toward the central Mediterranean can be partially explained by the well-defined Siculo-Tunisian Strait, an ocean front identified as a barrier for gene flow in some marine species (i.e., Mejri et al, 2009 ). In addition, recent study based on 79 SNPs analysis suggested that the hatchery stocking program conducted in Corsica during the 1970s, using lobsters originated from the Atlantic coast of France, left the footprint of Atlantic ancestry in the contemporary population and impacted the genetic structure of the Corsican natural population ( Jenkins et al, 2020 ). Such a restocking impact by European lobster of Atlantic origin may additionally explain the observed discontinuity of genetic differentiation within the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Ryman-Laikre effects could initially decrease the effective population size of the local wild populations, then may reduce their genetic diversities or may change their genetic structure after release (Waples et al, 2016;Grant et al, 2017). Moreover, introgression (gene flow) from hatchery-reared individuals, caused by artificial release or escape from aquaculture facilities, may alter local population structures and composition, or even replace them (Jenkins et al, 2020). This is a serious concern for cultured Atlantic salmon (Glover et al, 2017), gilthead sea bream (Sparus aurata) and European sea bass (Dicentrarchus labrax) (Arechavala-Lopez et al, 2018).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…More recently, studies have used up to 14 microsatellite loci to assert effective panmixia throughout regional seas (the Skagerrak—Huserbråten et al, 2013; the Irish Sea—Watson et al, 2016; the Western Channel and Celtic Sea—Ellis et al, 2017; the Adriatic—Pavičić et al, 2020), as well as evidence of spatial genetic structuring, with restricted connectivity apparent between Scandinavia and continental Atlantic coasts (Ellis et al, 2017), and between the Adriatic, Aegean and Tyrrhenian seas (Pavičić et al, 2020). Most recently, 79 highly differentiated single nucleotide polymorphisms (SNPs) identified a genetic cline of variation across open Atlantic coasts (Jenkins et al, 2019), and detected individuals of Atlantic descent introduced to the Mediterranean (Jenkins et al, 2020). By comparison, crawfish are less well researched.…”
Section: Introductionmentioning
confidence: 99%